Spatially Dense 3D Facial Heritability and Modules of Co-heritability in a Father-Offspring Design - Hoskens, Hanne; Li, Jiarui; Indencleef, Karlijne; Gors, Dorothy; Larmuseau, Maarten H. D.; Richmond, Stephen; Zhurov, Alexei I.; Hens, Greet; Peeters, Hilde; Claes, Peter (Frontiers in Genetics, 2018)
Introduction The human face is a complex trait displaying a strong genetic component as illustrated by various studies on facial heritability. Most of these start from sparse descriptions of facial shape using a limited set of landmarks. Subsequently, facial features are preselected as univariate measurements or principal components and the heritability is estimated for each of these features separately. However, none of these studies investigated multivariate facial features, nor the co-heritability between different facial features. Here we report a spatially-dense multivariate analysis of facial heritability and co-heritability starting from data from fathers and their children available within ALSPAC. Additionally, we provide an elaborate overview of related craniofacial heritability studies. Methods In total, 3D facial images of 762 father-offspring pairs were retained after quality control. An anthropometric mask was applied to these images to establish spatially-dense quasi-landmark configurations. Partial least squares regression was performed and the (co-)heritability for all quasi-landmarks ( 7160) was computed as twice the regression coefficient. Subsequently, these were used as input to a hierarchical facial segmentation, resulting in the definition of facial modules that are internally integrated through the biological mechanisms of inheritance. Finally, multivariate heritability estimates were obtained for each of the resulting modules. Results Nearly all modular estimates reached statistical significance under 1,000,000 permutations and after multiple testing correction (p <= 1.3889 × 10-3), displaying low to high heritability scores. Particular facial areas showing the greatest heritability were similar for both sons and daughters. However, higher estimates were obtained in the former. These areas included the global face, upper facial part (encompassing the nasion, zygomas and forehead) and nose, with values reaching 82% in boys and 72% in girls. The lower parts of the face only showed low to moderate levels of heritability. Conclusions In this work, we refrain from reducing facial variation to a series of individual measurements and analyze the heritability and co-heritability from spatially-dense landmark configurations at multiple levels of organization. Finally, a multivariate estimation of heritability for global-to-local facial segments is reported. Knowledge of the genetic determination of facial shape is useful in the identification of genetic variants that underlie normal-range